Crude Oil Importation and Exportation in Nigeria: An Exploratory and Comparative Study - Oguntunde, P. E.; Ojo, O. O.; Oguntunde, O. A.; Okagbue, H. I. (Engineering, Technology & Applied Science Research, 2018)
Nigeria is an oil producing country and crude oil is an important asset to its economy. This research focuses on the analysis of importation and exportation of crude oil products (measured in million barrels). Comparisons between the total importation and exportation were made and descriptive analysis was performed on the crude oil components. Poisson regression was used to establish the relationship between total importation and the importation of the petroleum products under consideration. The results show that Nigeria makes more importation than exportation of these products.